A case of recurrent massive thickening of the gastric wall caused by pancreatitis of the gastric ectopic pancreas: Detailed pathogenesis based on imaging. Issue 1 (24th November 2022) - Sasaki, Shun; Ota, Kazuhiro; Tanaka, Ryo; Imai, Yoshiro; Kojima, Yuichi; Akutagawa, Hiroshi; Iwatsubo, Taro; Sugawara, Noriaki; Hakoda, Akitoshi; Tanaka, Hironori; Mori, Yosuke; Lee, Sang‐Woong; et al.
Abstract: A 40‐year‐old Japanese male presented with epigastric pain and loss of appetite at a general hospital three years ago. Computed tomography revealed massive thickening of the gastric wall, and gastroscopy revealed diffuse erythema and edematous thickening of the gastric mucosa. Thereafter, epigastric pain and gastric wall thickening recurred frequently, causing an inability to intake food. Conservative treatment was marginally effective; therefore, a distal gastrectomy was performed. Postoperatively, the patient resumed food intake without complications. Histopathological examination of the surgical specimen revealed Heinrich type 1 gastric ectopic pancreas (EP) with pancreatitis. In this case, the gastric wall's massive thickening was caused by gastric EP's pancreatitis. Although there are some reports of pancreatitis of gastric EP, there are no detailed reports of endoscopic findings, including endoscopic ultrasonography and the disease progression. Recurrent pancreatitis of EP leads to forming a septum within the gastric wall, resulting in a hematoma. Eventually, irreversible narrowing of the gastric lumen may occur, as observed in the present case. We consider this an important case report presenting detailed pathogenesis supported by endoscopic and pathohistological findings of surgical specimens. Our study will help in the early diagnosis and better management of the condition.